Clinicohematological Profile of Pancytopenia Patients in Tertiary Care Hospital - Deepika Wadhera; Priyanka Naryal; Tripti Mishra; Jaskirat Singh; Irbinder K. Bali (Journal of Pharmacy and Bioallied Sciences)
Introduction: Pancytopenia is a common hematological problem characterized by anemia, leucopenia, and thrombocytopenia. It can be a serious and life-threatening illness. Aim: The objective of this study is to study the clinical presentation and hematological profile in pancytopenia patients. Material and Methods: The prospective study was done on 50 pancytopenia patients in a tertiary care hospital and the hematological profile was studied. All the cases with hemoglobin [Hb] less than 13 gm/dL in male and female <12 g/dL, total leukocyte count [TLC] less than 4000/cumm, and platelet count less than 150,000/cumm were included in the study. Result: It was observed that the majority of the cases had hypercellular marrow [40%], 34% normocellular, and 26% hypocellular marrow. Males [52%] were affected more as compared to females [48%]. Megaloblastic erythroid hyperplasia was found to be the commonest cause for pancytopenia [40%], followed by normoblastic erythroid hyperplasia [5.71%], non-Hodgkin lymphoma [11.42%], acute leukemia [2.85%], MDS [2.85%], malaria [2.85%], hypersplenism 2.85%], lymphoid malignancy [2.85%], focal gelatinous [2.85%], AML [2.85%], megakaryocytic thrombocytopenia [2.85%], and plasma cell myeloma [2.85%]. Conclusion: It was concluded that the detailed hematological investigations, a thorough clinical examination with hematological studies and bone marrow study is important for understanding the disease process and diagnosing the causes of pancytopenia.